Infrastructure in NW Russia - Potential development : A Pre-feasibility Study with Special Reference to Winter Transportation, Concrete Structures, and Timber Structures - Elfgren, Lennart; Fransson, Lennart; Täljsten, Björn (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2000)
In co-operation with a Finnish Group of researchers a pre-feasibility study was undertaken regarding potential development of the Infrastructure in NW Russia. Special emphasis was given: Winter Transportation and Reinforcement of Load Bearing Ice Covers; Concrete Construction and Strengthening of Concrete Structures; Timber Construction and Mechanical Wood Industry Development; and Energy Conservation and Industrial Energy Development. Based on the study three Russian-Swedish co-operation projects have started: - Load Bearing Ice Covers (Literature Survey) - Forces caused by Ice Crushing against Off-Shore Structures (EC funded Research Project) - Strengthening of a Bridge. Co-operation Stabilator/Skanska - Arkhangelsk Road Swedish Council for Building Research (BFR), Project 970270 - 8 Research Council of North Bothnia (Norrbottens forskningsråd), Project 97/014